Development Of Children's Activity Sheets Based On Aceh Cultural Diversity For Early Childhood Education - Noval Fuadi (Journal of Education and Teaching Learning, 2022)
This development research aims to produce a Children's Activity Sheet based on local cultural diversity, especially Aceh. This type of research is Research and Development (R&D) with the development model used according to Borg and Gall. The instrument used to measure the validity aspect of the Children's Activity Sheet is an assessment questionnaire by material experts, media experts, and linguists. The results showed that the Children's Activity Sheet was suitable to be used as teaching material, this was based on the assessment score obtained through the assessment score from the material expert getting a percentage of 83.33% with appropriate criteria, the assessment score from a linguist getting a percentage of 80% with the criteria feasible, and the assessment score from media experts gets a percentage of 93.18% with appropriate criteria. In the field trial, the percentage of attractiveness of the Children's Activity Sheet got a percentage of 93.75% with proper criteria. Based on the results of expert validation and product testing, the researcher can conclude that the Children's Activity Sheet is very suitable to be used as teaching material.